Composite particles for electrochemical device functional layer, binder composition for electrochemical device functional layer, conductive paste for electrode mixture layer, slurry for electrode mixture layer, electrode for electrochemical device, and electrochemical device

Composite particles with a melamine compound core and functional-group-containing polymer shell address safety and high-temperature storage challenges in electrochemical devices by enhancing adhesiveness and suppressing thermal runaway.

JP7600982B2Active Publication Date: 2024-12-17ZEON CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021509137
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-03-26
Filing Date
2020-03-17
Publication Date
2024-12-17
Estimated Expiration
2040-03-17

AI Technical Summary

Technical Problem

Existing electrochemical devices face challenges in ensuring safety and maintaining high-temperature storage characteristics due to thermal runaway caused by short circuits, despite incorporating organic compounds that generate nonflammable gases to suppress thermal runaway.

Method used

The use of composite particles with a core-shell structure, where the core contains a melamine compound and the shell is a polymer with functional groups, forming a functional layer that enhances adhesiveness and safety while improving high-temperature storage characteristics.

Benefits of technology

The composite particles with a core-shell structure provide excellent adhesiveness and safety, effectively suppressing thermal runaway and maintaining electrochemical device performance at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600982000004
    Figure 0007600982000004
  • Figure 0007600982000001
    Figure 0007600982000001
  • Figure 0007600982000002
    Figure 0007600982000002
Patent Text Reader

Abstract

The purpose of the present invention is to provide a novel technology related to electrochemical elements, which enables an electrochemical element to exhibit excellent high temperature storage characteristics, while sufficiently ensuring adhesion of a functional layer and safety of the electrochemical element. Each one of composite particles for electrochemical element functional layers according to the present invention is provided with: a core particle which contains a melamine compound; and a shell polymer which covers at least a part of the outer surface of the core particle, while having at least one group that is selected from the group consisting of a nitrile group, a carboxylic acid group, a hydroxyl group, a sulfonic acid group, an aldehyde group and an amide group.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to composite particles for electrochemical device functional layers, a binder composition for electrochemical device functional layers, a conductive paste for electrode mixture layers, a slurry for electrode mixture layers, electrodes for electrochemical devices, and electrochemical devices. [Background technology]

[0002] Electrochemical elements such as lithium ion secondary batteries, electric double layer capacitors, and lithium ion capacitors are small, lightweight, have high energy density, and can be repeatedly charged and discharged, and are used in a wide range of applications. Electrochemical elements generally include a plurality of electrodes and element members such as separators that isolate the electrodes to prevent internal short circuits.

[0003] As the element components of an electrochemical element, components are used that include a binder capable of imparting adhesiveness, and optionally have a functional layer that includes particles (hereinafter referred to as "functional particles") that are blended to enable the element components to exhibit a desired function. Specifically, the separator for the electrochemical element is provided with an adhesive layer containing a binder on a separator substrate, or a porous membrane layer containing a binder and non-conductive particles as functional particles. The electrode for the electrochemical element is provided with an electrode mixture layer containing a binder and electrode active material particles as functional particles on a current collector, or an electrode substrate provided with an electrode mixture layer on a current collector, and further provided with the above-mentioned adhesive layer or porous membrane layer.

[0004] In order to prevent an internal short circuit in an electrochemical element and ensure safety, attempts have been made to improve separators as element components. For example, Patent Document 1 reports that the safety of an electrochemical element can be improved by using a separator for an electrochemical element having a predetermined number of separator layers. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2016-181324 A Summary of the Invention [Problem to be solved by the invention]

[0006] In recent years, due to the diversification of applications of electrochemical elements, there has been a demand for new technologies that can ensure a higher level of safety by suppressing thermal runaway, such as abnormal heat generation and fire caused by short circuits between electrodes. In response to the above demands, the present inventors have investigated a method of incorporating an organic compound that decomposes at high temperatures to generate a non-flammable gas (nitrogen, carbon dioxide, carbon monoxide, ammonia, water vapor, etc.) in the functional layer that constitutes the element member of the electrochemical element. By incorporating such an organic compound in the functional layer, it becomes possible to suppress thermal runaway by generating a non-flammable gas even if the inside of the electrochemical element becomes abnormally hot due to a short circuit between the electrodes. The inventor then attempted to form a functional layer by applying a slurry obtained by dispersing and / or dissolving the organic compound and the binder in a solvent onto a substrate and drying the coating. However, it became clear that while a device member having a functional layer thus obtained can provide sufficient safety to an electrochemical device, an electrochemical device including the device member may have a problem in that the capacity decreases when stored at high temperatures for a long period of time (i.e., the high-temperature storage characteristics are poor).

[0007] Therefore, an object of the present invention is to provide a new technology relating to electrochemical elements that can provide the electrochemical element with excellent high-temperature storage characteristics while sufficiently ensuring the adhesion of the functional layer and the safety of the electrochemical element. [Means for solving the problem]

[0008] The present inventors have conducted extensive research to solve the above problems. As an organic compound that decomposes at high temperatures to generate a non-flammable gas, the present inventors have focused on melamine compounds. The present inventors have found that a functional layer can be obtained by forming a functional layer using composite particles in which a part or all of the outer surface of a particle containing a melamine compound is coated with a specific polymer, and that a device member including the functional layer can improve high-temperature storage characteristics while fully ensuring the safety of an electrochemical device, thereby completing the present invention.

[0009] That is, the present invention aims to advantageously solve the above problems, and the composite particle for electrochemical element functional layer of the present invention is characterized by comprising a core particle containing a melamine compound, and a shell polymer covering at least a part of the outer surface of the core particle and having at least one selected from the group consisting of a nitrile group, a carboxylic acid group, a hydroxyl group, a sulfonic acid group, an aldehyde group, and an amide group. In this way, by using a composite particle having a core-shell structure in which the outer surface of a core particle containing a melamine compound is covered with a shell polymer having at least one of the above-mentioned functional groups, a functional layer with excellent adhesiveness can be formed, and by using an element member having the functional layer, an electrochemical element with sufficient safety and excellent high-temperature storage characteristics can be manufactured.

[0010] In the composite particle for an electrochemical device functional layer of the present invention, the shell polymer preferably has an electrolyte swelling degree of 100% by mass or more and 600% by mass or less. The "electrolyte swelling degree" is the swelling degree when immersed in a measurement electrolyte at 60°C for 72 hours. The measurement electrolyte is a mixed solvent obtained by mixing ethylene carbonate and diethyl carbonate in a mass ratio of ethylene carbonate / diethyl carbonate = 3 / 7, and further adding 2 volume % of vinylene carbonate, and suspending LiPF 6The shell polymer is dissolved in the electrolyte solution at a concentration of 1.0 mol / L. If the swelling degree of the shell polymer when immersed in the electrolyte solution for measurement at 60° C. for 72 hours is within the above-mentioned range, the high-temperature storage characteristics of the electrochemical device can be further improved. In the present invention, the "degree of swelling in an electrolyte solution" can be measured by the method described in more detail in the Examples of this specification.

[0011] The composite particle for an electrochemical device functional layer of the present invention preferably has a thermal decomposition onset temperature of 120° C. or more and 500° C. or less. If the thermal decomposition onset temperature of the composite particle is within the above-mentioned range, the adhesiveness of the functional layer can be further improved while the safety of the electrochemical device can be more satisfactorily ensured. In the present invention, the "thermal decomposition onset temperature" can be measured by the method described in the Examples of this specification.

[0012] The present invention also aims to advantageously solve the above problems, and the binder composition for an electrochemical device functional layer of the present invention is characterized by containing any of the composite particles for a non-aqueous secondary battery functional layer of the present invention described above and a solvent. By using a binder composition containing any of the composite particles described above and a solvent, a functional layer with excellent adhesiveness can be formed, and by using a device member including the functional layer, an electrochemical device with sufficient safety and excellent high-temperature storage characteristics can be manufactured.

[0013] Here, the binder composition for an electrochemical element functional layer of the present invention preferably further contains a binder for a functional layer. By using a binder composition further containing a binder for a functional layer, the adhesion of the functional layer can be further improved.

[0014] In the binder composition for an electrochemical element functional layer of the present invention, the binder for the functional layer is preferably a polymer having at least one selected from the group consisting of a carboxylic acid group, a hydroxyl group, a nitrile group, an amino group, an epoxy group, an oxazoline group, an isocyanate group, a sulfonic acid group, an ester group, and an amide group. If a polymer having at least one of the above-mentioned functional groups is used as the binder for the functional layer, the adhesiveness of the functional layer can be further improved.

[0015] The present invention also aims to advantageously solve the above problems, and the conductive material paste for an electrode mixture layer of the present invention is characterized in that it contains any one of the binder compositions for an electrochemical element functional layer of the present invention described above and a conductive material. By using a conductive material paste containing any one of the binder compositions described above and a conductive material, an electrode mixture layer with excellent adhesiveness can be formed, and by using an electrode including the electrode mixture layer, an electrochemical element with sufficient safety and excellent high-temperature storage characteristics can be manufactured.

[0016] The present invention also aims to advantageously solve the above problems, and the slurry for an electrode mixture layer of the present invention is characterized in that it contains the above-mentioned conductive material paste for an electrode mixture layer of the present invention and electrode active material particles. By using a slurry containing the above-mentioned conductive material paste and electrode active material particles, an electrode mixture layer with excellent adhesiveness can be formed, and by using an electrode including the electrode mixture layer, an electrochemical element with sufficient safety and excellent high-temperature storage characteristics can be manufactured.

[0017] The present invention also aims to advantageously solve the above problems, and the electrode for an electrochemical element of the present invention is an electrode for an electrochemical element comprising an electrode mixture layer on a current collector, the electrode mixture layer being a dried product of the above-mentioned slurry for the electrode mixture layer of the present invention. The electrode mixture layer made of the dried product of the above-mentioned slurry for the electrode mixture layer can firmly adhere to the current collector, and by using an electrode comprising the electrode mixture layer, an electrochemical element can be manufactured that is sufficiently safe and has excellent high-temperature storage characteristics.

[0018] The present invention also aims to advantageously solve the above problems, and provides an electrochemical device comprising the above-mentioned electrode for electrochemical devices of the present invention. The electrochemical device comprising the above-mentioned electrode is sufficiently safe and has excellent high-temperature storage properties. Effect of the Invention

[0019] According to the present invention, it is possible to provide composite particles for electrochemical element functional layers and a binder composition for electrochemical element functional layers that can provide the electrochemical element with excellent high-temperature storage properties while fully ensuring the adhesion of the functional layer and the safety of the electrochemical element. Furthermore, according to the present invention, it is possible to provide a conductive paste for an electrode mixture layer and a slurry for an electrode mixture layer that can sufficiently ensure the adhesion of the electrode mixture layer and the safety of the electrochemical element, while enabling the electrochemical element to exhibit excellent high-temperature storage characteristics. Furthermore, according to the present invention, it is possible to provide an electrode for an electrochemical device that can ensure the safety of the electrochemical device while enabling the electrochemical device to exhibit excellent high-temperature storage characteristics. Furthermore, according to the present invention, it is possible to provide an electrochemical element which is sufficiently safe and has excellent high-temperature storage characteristics. [Brief description of the drawings]

[0020] [Figure 1] FIG. 1 is a cross-sectional view illustrating a structure of an example of a composite particle of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Hereinafter, an embodiment of the present invention will be described in detail. Here, the composite particles for electrochemical element functional layers of the present invention are used for the production of functional layers of electrochemical elements (electrode mixture layers, porous membrane layers, adhesive layers, etc.), and can be used, for example, for the preparation of the binder composition for electrochemical element functional layers of the present invention. The binder composition for an electrochemical element functional layer of the present invention can be used, for example, when preparing the conductive paste for an electrode mixture layer of the present invention. The conductive paste for an electrode mixture layer of the present invention can be used when preparing the slurry for an electrode mixture layer of the present invention. Furthermore, the electrode for electrochemical elements of the present invention can be used as an electrode for electrochemical elements such as lithium ion secondary batteries, electric double layer capacitors, and lithium ion capacitors, and has an electrode mixture layer formed using the slurry for electrode mixture layers of the present invention. In addition, the electrochemical device of the present invention comprises the electrode for electrochemical devices of the present invention.

[0022] (Composite particles for electrochemical element functional layers) The composite particle of the present invention comprises a core particle and a shell polymer that is (physically and / or chemically) adhered to the core particle to cover at least a part of the outer surface of the core particle. Here, in the composite particle of the present invention, the core particle contains a melamine compound, and the shell polymer has at least one functional group selected from the group consisting of a nitrile group, a carboxylic acid group, a hydroxyl group, a sulfonic acid group, an aldehyde group, and an amide group (hereinafter, these functional groups may be collectively referred to as a "shell functional group").

[0023] Furthermore, the composite particle of the present invention has a core-shell structure in which a core particle containing a melamine compound is coated with a shell polymer having the above-mentioned shell functional group, and therefore the composite particle of the present invention makes it possible to produce a functional layer with excellent adhesion, and an electrochemical element that is fully safe and has excellent high-temperature storage characteristics.

[0024] Here, the reason why the above-mentioned effects are achieved by using the composite particles of the present invention is not clear, but is presumed to be as follows. First, due to the binding ability of the melamine compound contained in the core particle and the binding ability of the shell functional group contained in the shell polymer, the composite particle of the present invention can be used to form a functional layer, thereby allowing the resulting functional layer to exhibit excellent adhesion. In addition, the melamine compound contained in the core particle not only contributes to improving the adhesion of the functional layer, but can also decompose and generate non-flammable gas when the inside of the electrochemical element becomes abnormally hot. Therefore, an electrochemical element having a functional layer formed using the composite particle of the present invention can suppress thermal runaway by generating non-flammable gas from the melamine compound even when the inside of the electrochemical element becomes abnormally hot due to a short circuit between the electrodes. On the other hand, the melamine compound contained in the core particle has a property of unintentionally causing a chemical reaction when it comes into contact with an electrolyte. In contrast, in the composite particle of the present invention, at least a part of the outer surface of the core particle containing the melamine compound is covered with a shell polymer, so that when a functional layer is formed using the composite particle of the present invention, contact between the melamine compound and the electrolyte is suppressed. Therefore, it is possible to suppress a chemical reaction that may occur between the melamine compound and the electrolyte inside the electrochemical element, and to sufficiently ensure the high-temperature storage characteristics of the electrochemical element. In addition, the composite particles of the present invention are preferably used as a functional layer, particularly for preparing an electrode mixture layer. By disposing the composite particles containing a melamine compound in the electrode mixture layer, the melamine compound can act in the vicinity of the conductive material and the electrode active material particles that are thermally unstable and may release oxygen, which is a flammable substance. Therefore, it is possible to quickly destroy the electrode structure and cut off the conductive path, and the high level of safety of the electrochemical element can be further ensured.

[0025] <Core-shell structure> Here, the composite particle of the present invention has the above-mentioned core-shell structure including a core portion and a shell portion. In this core-shell structure, the shell polymer of the shell portion may entirely or partially cover the outer surface of the core particle of the core portion.

[0026] An example of the cross-sectional structure of a composite particle in which the shell polymer covers the entire outer surface of the core particle is shown in Fig. 1. In Fig. 1, a composite particle 100 has a core-shell structure including a core particle 110 as a core portion and a shell polymer 120 as a shell portion. Here, the core particle 110 is present inside the shell polymer 120 in this composite particle 100. The shell polymer 120 also covers the outer surface 110S of the core particle 110, and is usually present on the outermost side in the composite particle 100. In Fig. 1, the shell polymer 120 covers the entire outer surface 110S of the core particle 110.

[0027] <Core particle> The core particle forming the core portion of the composite particle of the present invention contains at least a melamine compound, and may contain components (other compounds) other than the melamine compound. That is, the core particle may be a particle consisting of only a melamine compound, or a particle consisting of a melamine compound and other compounds.

[0028] <<Melamine compounds>> The melamine compound includes melamine, a derivative of melamine, and a salt thereof. Examples of the melamine and a derivative of melamine include a compound represented by the following formula (I).

[0029] [ka]

[0030] In formula (I), each A is independently a hydroxyl group or -NR 1 R 2 (R 1 and R 2 Each independently represents a hydrogen atom, a hydrocarbon group, or a hydroxyl group-containing hydrocarbon group. 1 If there are multiple, there are multiple R 1 may be the same or different, R 2 If there are multiple, there are multiple R 2may be the same or different.

[0031] Here, R 1 and R 2 In the hydrocarbon group and hydroxyl group-containing hydrocarbon group, when the number of carbon atoms is 2 or more, one or more oxygen atoms (-O-) may be interposed between the carbon atoms (however, when two or more oxygen atoms are interposed, they are not adjacent to each other). 1 and R 2 The number of carbon atoms in the hydrocarbon group and the hydroxyl group-containing hydrocarbon group is not particularly limited, but is preferably 1 or more and 5 or less.

[0032] Furthermore, salts of melamine and melamine derivatives are not particularly limited, but include sulfates, cyanurates, polyphosphates, and the like.

[0033] From the viewpoint of further improving the adhesion of the functional layer, the melamine compound is preferably melamine, ammeline, ammelide, or a salt thereof with cyanuric acid, and more preferably melamine or a cyanuric acid salt of melamine (melamine cyanurate). The melamine compound may be used alone or in combination of two or more kinds in any ratio.

[0034] Here, from the viewpoint of further improving the adhesion of the functional layer while better ensuring the safety of the electrochemical element, the proportion of the melamine compound in the core particle is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, particularly preferably 95% by mass or more, and most preferably 100% by mass (i.e., the core particle consists only of the melamine compound), with the mass of the core particle (in other words, the total mass of the melamine compound and other compounds) being 100% by mass.

[0035] <<Other compounds>> The other compounds that the core particles may optionally contain are not particularly limited as long as they do not significantly impede the effects of the present invention. For example, the core particles may contain an organic compound that decomposes at high temperatures to generate a non-flammable gas, other than a melamine compound. Examples of such organic compounds include azobisisobutyronitrile, p-toluenesulfonylhydrazide, 5-methyl-1H-benzotriazole, oxybisbenzenesulfonylhydrazide, trihydrazinetriazine, azodicarbonamide, hydrazodicarbonamide, dinitrosopentamethylenetetramine, p-toluenesulfonylsemicarbazide, and p,p'-oxybisbenzenesulfonylsemicarbazide. The other compounds may be used alone or in combination of two or more at any ratio.

[0036] <<Proportion of core particles in composite particles>> In the composite particle, the ratio of the core particle to the total of the core particle and the shell polymer is preferably 50.0% by mass or more, more preferably 60.0% by mass or more, even more preferably 70.0% by mass or more, particularly preferably 80.0% by mass or more, and preferably 99.9% by mass or less, more preferably 95.0% by mass or less, and even more preferably 90.0% by mass or less, based on the total of the core particle and the shell polymer being 100% by mass. If the ratio of the core particle to the total of the core particle and the shell polymer is 50.0% by mass or more, the safety of the electrochemical device can be more satisfactorily ensured, and if it is 99.9% by mass or less, the high-temperature storage characteristics of the electrochemical device can be further improved.

[0037] <Shell polymer> The shell polymer is a polymer that can adhere to the outer surface of the core particle and thereby bond physically or chemically to the core particle, thereby covering at least a part of the outer surface of the core particle. The shell polymer is integrated with the core particle to form a composite particle, which is a fine particle.

[0038] <<Functional groups of shell polymer>> The shell polymer must have at least one shell functional group selected from the group consisting of a nitrile group, a carboxylic acid group, a hydroxyl group, a sulfonic acid group, an aldehyde group, and an amide group. Polymers having these shell functional groups can not only impart adhesiveness to the functional layer, but also have good affinity with the above-mentioned core particles containing a melamine compound, so that they can adhere to the core particles and cover the outer surface thereof well. The shell polymer may have one type of shell functional group, or may have two or more types of shell functional groups. From the viewpoint of further improving the high-temperature storage properties of the electrochemical element by further ensuring the affinity with the core particles, the shell functional group is preferably a nitrile group, a carboxylic acid group, or a hydroxyl group, and more preferably a nitrile group or a carboxylic acid group. From the viewpoint of further improving the adhesiveness of the functional layer, the shell functional group is more preferably a sulfonic acid group. The shell functional group may be in the form of a salt (such as a sodium salt).

[0039] Here, the method of introducing the above-mentioned shell functional group into the shell polymer is not particularly limited. For example, a polymer may be prepared using a monomer having the above-mentioned shell functional group (shell functional group-containing monomer) to obtain a polymer containing a shell functional group-containing monomer unit, or an arbitrary polymer may be modified to obtain a polymer into which the above-mentioned shell functional group has been introduced, but the former is preferred. That is, from the viewpoint of further improving the high-temperature storage characteristics of the electrochemical element, the shell polymer preferably contains at least one of a nitrile group-containing monomer unit, a carboxylic acid group-containing monomer unit, a hydroxyl group-containing monomer unit, a sulfonic acid group-containing monomer unit, an aldehyde group-containing monomer unit, and an amide group-containing monomer unit, more preferably contains at least one of a nitrile group-containing monomer unit, a carboxylic acid group-containing monomer unit, and a hydroxyl group-containing monomer unit, and even more preferably contains at least one of a nitrile group-containing monomer unit and a carboxylic acid group-containing monomer unit. In addition, from the viewpoint of further improving the adhesiveness of the functional layer, the shell polymer preferably contains a sulfonic acid group-containing monomer unit. In the present invention, the phrase "containing a monomer unit" means that "a polymer obtained by using the monomer contains a repeating unit derived from the monomer".

[0040] [Nitrile group-containing monomer unit] The nitrile group-containing monomer capable of forming the nitrile group-containing monomer unit may be an α,β-ethylenically unsaturated nitrile monomer. Specifically, the α,β-ethylenically unsaturated nitrile monomer is not particularly limited as long as it is an α,β-ethylenically unsaturated compound having a nitrile group, and examples thereof include acrylonitrile; α-halogenoacrylonitrile such as α-chloroacrylonitrile and α-bromoacrylonitrile; α-alkylacrylonitrile such as methacrylonitrile and α-ethylacrylonitrile; and the like. The nitrile group-containing monomer may be used alone or in combination of two or more kinds at any ratio.

[0041] [Carboxylic acid group-containing monomer unit] Examples of the carboxylic acid group-containing monomer capable of forming the carboxylic acid group-containing monomer unit include monocarboxylic acids and derivatives thereof, dicarboxylic acids and acid anhydrides thereof, and derivatives thereof. Examples of the monocarboxylic acid include acrylic acid, methacrylic acid, and crotonic acid. Examples of the monocarboxylic acid derivatives include 2-ethylacrylic acid, isocrotonic acid, α-acetoxyacrylic acid, β-trans-aryloxyacrylic acid, and α-chloro-β-E-methoxyacrylic acid. The dicarboxylic acids include maleic acid, fumaric acid, and itaconic acid. Examples of dicarboxylic acid derivatives include methylmaleic acid, dimethylmaleic acid, phenylmaleic acid, chloromaleic acid, dichloromaleic acid, fluoromaleic acid, and maleic acid monoesters such as nonyl maleate, decyl maleate, dodecyl maleate, octadecyl maleate, and fluoroalkyl maleate. Examples of the acid anhydrides of dicarboxylic acids include maleic anhydride, acrylic anhydride, methylmaleic anhydride, and dimethylmaleic anhydride. In addition, as the carboxylic acid group-containing monomer, an acid anhydride that generates a carboxylic acid group by hydrolysis can also be used. Among them, as the carboxylic acid group-containing monomer, acrylic acid and methacrylic acid are preferable. In addition, as the carboxylic acid group-containing monomer, one type may be used alone, or two or more types may be used in combination at any ratio.

[0042] [Hydroxyl-containing monomer units] Examples of hydroxyl group-containing monomers capable of forming a hydroxyl group-containing monomer unit include ethylenically unsaturated alcohols such as (meth)allyl alcohol, 3-butene-1-ol, and 5-hexene-1-ol; alkanol esters of ethylenically unsaturated carboxylic acids such as 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, di-2-hydroxyethyl maleate, di-4-hydroxybutyl maleate, and di-2-hydroxypropyl itaconate; and compounds of the general formula: CH 2 =CR a -COO-(C q H 2q O) p -H (wherein p is an integer of 2 to 9, q is an integer of 2 to 4, R arepresents a hydrogen atom or a methyl group) and (meth)acrylic acid esters; mono(meth)acrylic acid esters of dihydroxy esters of dicarboxylic acids such as 2-hydroxyethyl-2'-(meth)acryloyloxyphthalate and 2-hydroxyethyl-2'-(meth)acryloyloxysuccinate; vinyl ethers such as 2-hydroxyethyl vinyl ether and 2-hydroxypropyl vinyl ether; mono(meth)allyl ethers of alkylene glycols such as (meth)allyl-2-hydroxyethyl ether, (meth)allyl-2-hydroxypropyl ether, (meth)allyl-3-hydroxypropyl ether, (meth)allyl-2-hydroxybutyl ether, (meth)allyl-3-hydroxybutyl ether, (meth)allyl-4-hydroxybutyl ether, and (meth)allyl-6-hydroxyhexyl ether; diethylene glycol mono(meth)allyl ether, dipropylene glycol Examples of the hydroxyl group-containing monomer include polyoxyalkylene glycol mono(meth)allyl ethers such as glycol mono(meth)allyl ether; mono(meth)allyl ethers of halogen- and hydroxy-substituted (poly)alkylene glycols such as glycerin mono(meth)allyl ether, (meth)allyl-2-chloro-3-hydroxypropyl ether, and (meth)allyl-2-hydroxy-3-chloropropyl ether; mono(meth)allyl ethers of polyhydric phenols such as eugenol and isoeugenol and their halogen-substituted derivatives; (meth)allyl thioethers of alkylene glycols such as (meth)allyl-2-hydroxyethyl thioether and (meth)allyl-2-hydroxypropyl thioether; and amides having a hydroxyl group such as N-hydroxymethylacrylamide (N-methylolacrylamide), N-hydroxymethylmethacrylamide, N-hydroxyethylacrylamide, and N-hydroxyethylmethacrylamide. The hydroxyl group-containing monomer may be used alone or in combination of two or more kinds in any ratio. In the present invention, "(meth)allyl" means allyl and / or methallyl, and "(meth)acryloyl" means acryloyl and / or methacryloyl.

[0043] [Sulfonic acid group-containing monomer unit] Examples of sulfonic acid group-containing monomers capable of forming sulfonic acid group-containing monomer units include vinyl sulfonic acid, methyl vinyl sulfonic acid, (meth)allyl sulfonic acid, styrene sulfonic acid, (meth)acrylic acid-2-ethyl sulfonate, 2-acrylamido-2-methylpropanesulfonic acid, 3-allyloxy-2-hydroxypropanesulfonic acid, etc. The sulfonic acid group-containing monomers may be used alone or in combination of two or more kinds at any ratio.

[0044] [Aldehyde group-containing monomer unit] Examples of aldehyde group-containing monomers capable of forming aldehyde group-containing monomer units include acrolein, etc. The aldehyde group-containing monomers may be used alone or in combination of two or more kinds at any ratio.

[0045] [Amide group-containing monomer unit] Examples of the amide group-containing monomer capable of forming the amide group-containing monomer unit include acrylamide, methacrylamide, vinylpyrrolidone, etc. The amide group-containing monomer may be used alone or in combination of two or more kinds in any ratio.

[0046] Here, when the amount of all repeating units contained in the shell polymer is taken as 100% by mass, the content of the shell functional group-containing monomer unit in the shell polymer is preferably 20% by mass or more, more preferably 30% by mass or more, even more preferably 50% by mass or more, and particularly preferably 70% by mass or more, from the viewpoint of further improving the high-temperature storage characteristics of the electrochemical device. Note that the upper limit of the content of the shell functional group-containing monomer unit in the shell polymer is not particularly limited, and can be 100% by mass or less, or can be 99% by mass or less.

[0047] [Other repeating units] The shell polymer may contain repeating units (other repeating units) other than the above-mentioned shell functional group-containing monomer units. Examples of such other repeating units include, but are not limited to, aromatic vinyl monomer units such as styrene units, (meth)acrylic acid ester monomer units such as n-butyl acrylate units, aliphatic conjugated diene monomer units such as 1,3-butadiene units, and aliphatic conjugated diene monomer hydrogenated units obtained by hydrogenating aliphatic conjugated diene monomer units. The shell polymer may contain one type of other repeating unit, or may contain two or more types.

[0048] <<Preparation method of shell polymer>> In the present invention, the method for preparing the shell polymer is not particularly limited. The shell polymer is produced, for example, by polymerizing a monomer composition containing one or more types of monomers in an aqueous solvent, and optionally hydrogenating or modifying the monomer composition. The content ratio of each monomer in the monomer composition can be determined according to the content ratio of the desired monomer unit (repeating unit) in the polymer. The polymerization method is not particularly limited, and any method such as solution polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc. can be used. The polymerization reaction can be any reaction such as ionic polymerization, radical polymerization, living radical polymerization, various condensation polymerization, addition polymerization, etc. In addition, during polymerization, a known emulsifier or polymerization initiator can be used as necessary. Furthermore, hydrogenation and modification can be performed by known methods.

[0049] <<Type of shell polymer>> From the viewpoint of further improving the high-temperature storage characteristics of the electrochemical element, the shell polymer is preferably, for example, polyacrylonitrile (a polymer containing more than 50% by mass of acrylonitrile units), polyvinylpyrrolidone (a polymer containing more than 50% by mass of vinylpyrrolidone units), an acrylic acid-acrylamide copolymer (a polymer containing more than 50% by mass of acrylic acid units and acrylamide units in total), or an acrylic acid-3-allyloxy-2-hydroxypropanesulfonic acid copolymer (a polymer containing more than 50% by mass of acrylic acid units and 3-allyloxy-2-hydroxypropanesulfonic acid units in total), and more preferably, polyacrylonitrile, an acrylic acid-acrylamide copolymer, or an acrylic acid-3-allyloxy-2-hydroxypropanesulfonic acid copolymer.

[0050] <<Electrolyte swelling rate>> Here, the electrolyte swelling degree of the shell polymer is preferably 100% by mass or more, preferably 600% by mass or less, more preferably 500% by mass or less, even more preferably 400% by mass or less, and particularly preferably 300% by mass or less. If the electrolyte swelling degree is within the above-mentioned range, swelling of the shell polymer in the electrolyte is suppressed, thereby suppressing chemical reaction between the melamine compound in the core particle and the electrolyte, and thus the high-temperature storage characteristics of the electrochemical element can be further improved. The swelling degree of the shell polymer in an electrolyte solution can be adjusted, for example, by changing the types and / or ratio of monomers used in preparing the shell polymer.

[0051] <<Proportion of shell polymer in composite particles>> In the composite particle, the proportion of the shell polymer in the total of the core particle and the shell polymer is preferably 0.1% by mass or more, more preferably 5.0% by mass or more, and even more preferably 8.5% by mass or more, and preferably 50.0% by mass or less, more preferably 40.0% by mass or less, even more preferably 30.0% by mass or less, and particularly preferably 20.0% by mass or less, based on 100% by mass of the total of the core particle and the shell polymer. If the proportion of the shell polymer in the total of the core particle and the shell polymer is 0.1% by mass or more, the high-temperature storage characteristics of the electrochemical device can be further improved, and if it is 50.0% by mass or less, the safety of the electrochemical device can be further ensured.

[0052] <Method of preparing composite particles> The method for preparing composite particles having a structure in which a core particle is coated with a shell polymer is not particularly limited as long as it is possible to form a predetermined core-shell structure by granulating a material that forms the core portion (core material) and a material that forms the shell portion (shell material). Examples of the method include a fluidized bed granulation method, a spray granulation method, a coagulant precipitation method, a pH precipitation method, and a dry mixing method. As a method for preparing the composite particles, a spray granulation method and a dry mixing method are preferred.

[0053] <<Spray granulation method>> In the spray granulation method, a slurry composition containing a core material, a shell material, and an aqueous medium such as water is spray-dried to obtain fine particles having a predetermined core-shell structure. In particular, the core material, the shell material, and an aqueous medium are mixed to prepare a slurry composition, and the slurry composition is sprayed and dried to granulate the composite particles.

[0054] Here, examples of means for mixing the core material, shell material, and aqueous medium include mixers such as ball mills, sand mills, bead mills, pigment dispersers, crushers, ultrasonic dispersers, homogenizers, and planetary mixers. Mixing is usually performed at room temperature to 80° C. for 10 minutes to several hours. The solid content concentration of the slurry composition obtained by the above-mentioned mixing is not particularly limited, but is preferably 1% by mass or more, more preferably 5% by mass or more, and particularly preferably 10% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, and particularly preferably 30% by mass or less.

[0055] The slurry composition obtained by the above-mentioned mixing is sprayed using a spray dryer, and the sprayed droplets of the slurry composition are dried inside a drying tower. This allows the shell material to be bonded to the outer surface of the core material contained in the droplets, and composite particles can be obtained in which at least a part of the outer surface of the core particle is covered with the shell polymer. The temperature of the slurry composition to be sprayed is usually room temperature, but it may be heated to a temperature higher than room temperature. The hot air temperature during spray drying is usually 80 to 250°C, preferably 100 to 200°C.

[0056] <<Dry mixing method>> In the dry mixing method, the core material and the shell material are mixed at a solid content of 80% by mass or more when mixed, and fine particles having a predetermined core-shell structure can be obtained. Here, examples of the method for dry mixing the core material and the shell material include a container mixing method using a rocking mixer, a tumbler mixer, or the like, in which the container itself is shaken and / or rotated to mix the contents; a mechanical mixing method using a horizontal cylindrical mixer, a V-type mixer, a ribbon mixer, a conical screw mixer, a high-speed fluid mixer, a rotating disk mixer, a high-speed rotating blade mixer, or the like, which is a mixer having a stirring blade, a rotating disk, or a screw attached to a horizontal or vertical rotating shaft in the container; and an air flow mixing method in which a swirling air current caused by compressed gas is used to mix powders in a fluidized bed. In addition, mixers using these mechanisms can be used alone or in combination. In addition, after dry mixing, disintegration may be performed using a mortar or the like to the extent that agglomerations are loosened.

[0057] <Properties of composite particles> The composite particles preferably have a thermal decomposition onset temperature of 120°C or higher, more preferably 150°C or higher, even more preferably 200°C or higher, particularly preferably 260°C or higher, and preferably 500°C or lower, more preferably 400°C or lower, and even more preferably 350°C or lower. If the composite particles have a thermal decomposition onset temperature of 120°C or higher, the composite particles (particularly the core particles) can be prevented from thermally decomposing except at abnormally high temperatures, and the adhesion of the functional layer can be sufficiently improved. On the other hand, if the composite particles have a thermal decomposition onset temperature of 500°C or lower, the safety of the electrochemical element can be further ensured. The thermal decomposition starting temperature of the composite particles can be adjusted, for example, by changing the type and / or ratio of the melamine compound and other compounds optionally contained in the core particles, or by changing the ratio of the core particles (or shell polymer) to the total of the core particles and the shell polymer.

[0058] The moisture content of the composite particles is preferably 3.0% by mass or less, more preferably 1.0% by mass or less, even more preferably 0.5% by mass or less, particularly preferably 0.1% by mass or less, and most preferably 0% by mass (below the detection limit). The water content of the composite particles can be measured by the Karl Fischer method. Furthermore, as described above, in the composite particles, the shell polymer may cover the entire outer surface of the core particle, or may cover only a portion of it. However, the proportion of the shell polymer present on the outer surface of the composite particle (the proportion of the area of ​​the portions of the outer surface where the shell polymer is present relative to the entire area of ​​the outer surface of the composite particle; also referred to as the "coverage rate") is preferably 50% or more and 100% or less, and more preferably 70% or more and 100% or less, with the entire area of ​​the outer surface of the composite particle being 100%, from the viewpoint of ensuring sufficient high-temperature storage characteristics of the electrochemical element. In the present invention, the "covering rate" of a composite particle can be calculated as the average value of 10 arbitrarily selected particles by observing the composite particle as a particle aggregate under a scanning electron microscope. In addition, the volume average particle diameter D50 of the composite particles is preferably 0.01 μm or more, more preferably 0.10 μm or more, and is preferably 5.00 μm or less, more preferably 2.50 μm or less. In the present invention, the term "volume average particle diameter D50" refers to the particle diameter at which the cumulative volume calculated from the small diameter side is 50% in the particle size distribution (volume basis) measured by a laser diffraction method.

[0059] (Binder composition for electrochemical device functional layer) The binder composition of the present invention is a composition in which the composite particles of the present invention described above are dispersed in a solvent. The binder composition of the present invention may optionally contain a binder for a functional layer and other components. The binder composition of the present invention can be used to form a functional layer having excellent adhesiveness, and an electrochemical element having sufficient safety and excellent high-temperature storage characteristics can be manufactured by using an element member having the functional layer. In the binder composition for electrochemical element functional layer of the present invention, and the conductive material paste for electrode mixture layer of the present invention and the slurry for electrode mixture layer of the present invention described below (hereinafter, these may be collectively referred to as "binder composition, etc."), the composite particles maintain a core-shell structure in which at least a part of the outer surface of the core particle is covered with a shell polymer. However, in the binder composition, etc. of the present invention, a part of the shell polymer may be detached from the core particle and exist in a state dispersed and / or dissolved in the solvent separately from the composite particle.

[0060] <Solvent> Examples of the solvent for the binder composition include water and organic solvents. Examples of the organic solvent that can be used include acetonitrile, N-methylpyrrolidone, acetylpyridine, cyclopentanone, N,N-dimethylacetamide, dimethylformamide, dimethylsulfoxide, methylformamide, methylethylketone, furfural, and ethylenediamine. Among these, N-methylpyrrolidone (NMP) is the most preferable organic solvent from the viewpoints of ease of handling, safety, and ease of synthesis. The solvent may be used alone or in combination of two or more kinds.

[0061] <Binder for functional layer> The binder composition may further include a binder for the functional layer. If the functional layer is formed using a binder composition containing the binder for the functional layer in addition to the composite particles, the adhesiveness of the resulting functional layer can be further improved. In the present invention, the binder for the functional layer does not include a melamine compound.

[0062] <<Functional groups of binders for functional layers>> From the viewpoint of further improving the adhesiveness of the functional layer, the binder for the functional layer is preferably a polymer having at least one selected from the group consisting of a carboxylic acid group, a hydroxyl group, a nitrile group, an amino group, an epoxy group, an oxazoline group, an isocyanate group, a sulfonic acid group, an ester group, and an amide group (hereinafter, these functional groups may be collectively referred to as "binder functional groups"). The polymer constituting the binder for the functional layer may have one type of these binder functional groups, or may have two or more types. From the viewpoint of further improving the adhesiveness of the functional layer, the binder functional groups are preferably a carboxylic acid group, a hydroxyl group, and a nitrile group, and more preferably a carboxylic acid group and a nitrile group.

[0063] Here, the method of introducing the above-mentioned binder functional group into the binder for functional layer is not particularly limited.For example, the above-mentioned monomer having the binder functional group (monomer containing binder functional group) may be used to prepare a polymer, and the polymer containing the binder functional group-containing monomer unit may be obtained, or any polymer may be modified to obtain the polymer into which the above-mentioned binder functional group is introduced, and the former is preferred. That is, the binder for the functional layer preferably contains at least one of a carboxylic acid group-containing monomer unit, a hydroxyl group-containing monomer unit, a nitrile group-containing monomer unit, an amino group-containing monomer unit, an epoxy group-containing monomer unit, an oxazoline group-containing monomer unit, an isocyanate group-containing monomer unit, a sulfonic acid group-containing monomer unit, an ester group-containing monomer unit, and an amide group-containing monomer unit, more preferably contains at least one of a carboxylic acid group-containing monomer unit, a hydroxyl group-containing monomer unit, and a nitrile group-containing monomer unit, and further preferably contains at least one of a carboxylic acid group-containing monomer unit and a nitrile group-containing monomer unit.

[0064] [Carboxylic acid group-containing monomer unit] Examples of the carboxylic acid group-containing monomer capable of forming the carboxylic acid group-containing monomer unit include the same as those described above in the section "Composite particles for electrochemical element functional layer". The carboxylic acid group-containing monomer may be used alone or in combination of two or more kinds in any ratio.

[0065] [Hydroxyl-containing monomer units] Examples of the hydroxyl group-containing monomer capable of forming the hydroxyl group-containing monomer unit include those mentioned above in the section "Composite particles for electrochemical element functional layer". The hydroxyl group-containing monomer may be used alone or in combination of two or more kinds in any ratio.

[0066] [Nitrile group-containing monomer unit] The nitrile group-containing monomer capable of forming the nitrile group-containing monomer unit may be the same as those mentioned above in the section "Composite particles for electrochemical element functional layer". The nitrile group-containing monomer may be used alone or in combination of two or more kinds in any ratio.

[0067] [Amino group-containing monomer unit] Examples of amino group-containing monomers capable of forming amino group-containing monomer units include dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, aminoethyl vinyl ether, dimethylaminoethyl vinyl ether, etc. The amino group-containing monomers may be used alone or in combination of two or more kinds at any ratio. In the present invention, the term "(meth)acrylate" means acrylate and / or methacrylate.

[0068] [Epoxy group-containing monomer unit] The epoxy group-containing monomer capable of forming the epoxy group-containing monomer unit includes a monomer containing a carbon-carbon double bond and an epoxy group. Examples of the monomer containing a carbon-carbon double bond and an epoxy group include unsaturated glycidyl ethers such as vinyl glycidyl ether, allyl glycidyl ether, butenyl glycidyl ether, and o-allylphenyl glycidyl ether; monoepoxides of dienes or polyenes such as butadiene monoepoxide, chloroprene monoepoxide, 4,5-epoxy-2-pentene, 3,4-epoxy-1-vinylcyclohexene, and 1,2-epoxy-5,9-cyclododecadiene; 3,4-epoxy-1 alkenyl epoxides such as 1,2-butene, 1,2-epoxy-5-hexene, and 1,2-epoxy-9-decene; and glycidyl esters of unsaturated carboxylic acids such as glycidyl acrylate, glycidyl methacrylate, glycidyl crotonate, glycidyl-4-heptenoate, glycidyl sorbate, glycidyl linoleate, glycidyl-4-methyl-3-pentenoate, glycidyl ester of 3-cyclohexene carboxylic acid, and glycidyl ester of 4-methyl-3-cyclohexene carboxylic acid. The epoxy group-containing monomer may be used alone or in combination of two or more kinds in any ratio.

[0069] [Oxazoline group-containing monomer unit] Examples of oxazoline group-containing monomers capable of forming oxazoline group-containing monomer units include 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, 2-isopropenyl-5-methyl-2-oxazoline, 2-isopropenyl-5-ethyl-2-oxazoline, etc. The oxazoline group-containing monomers may be used alone or in combination of two or more at any ratio.

[0070] [Isocyanate group-containing monomer unit] Examples of isocyanate group-containing monomers capable of forming isocyanate group-containing monomer units include 2-acryloyloxyethyl isocyanate, 2-methacryloyloxyethyl isocyanate, etc. The isocyanate group-containing monomer units may be used alone or in combination of two or more kinds in any ratio.

[0071] [Sulfonic acid group-containing monomer unit] Examples of the sulfonic acid group-containing monomer that can form the sulfonic acid group-containing monomer unit include those mentioned above in the section "Composite particles for electrochemical element functional layer". The sulfonic acid group-containing monomer may be used alone or in combination of two or more kinds in any ratio.

[0072] [Ester group-containing monomer unit] As the ester group-containing monomer capable of forming the ester group-containing monomer unit, for example, a (meth)acrylic acid ester monomer can be used. Examples of the (meth)acrylic acid ester monomer include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, butyl acrylate such as n-butyl acrylate and t-butyl acrylate, octyl acrylate such as pentyl acrylate, hexyl acrylate, heptyl acrylate, and 2-ethylhexyl acrylate, acrylic acid alkyl esters such as nonyl acrylate, decyl acrylate, lauryl acrylate, n-tetradecyl acrylate, and stearyl acrylate; and Examples of the ester group-containing monomer include methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, butyl methacrylates such as n-butyl methacrylate and t-butyl methacrylate, octyl methacrylates such as pentyl methacrylate, hexyl methacrylate, heptyl methacrylate and 2-ethylhexyl methacrylate, and methacrylic acid alkyl esters such as nonyl methacrylate, decyl methacrylate, lauryl methacrylate, n-tetradecyl methacrylate and stearyl methacrylate. The ester group-containing monomer may be used alone or in combination of two or more kinds at any ratio. In the present invention, when a certain monomer has a binder functional group (or a shell functional group) other than an ester group, the monomer is not included in the ester group-containing monomer.

[0073] [Amide group-containing monomer unit] Examples of the amide group-containing monomer capable of forming the amide group-containing monomer unit include those mentioned above in the section "Composite particles for electrochemical element functional layer". The amide group-containing monomer may be used alone or in any combination of two or more kinds at any ratio.

[0074] Here, when the amount of all repeating units contained in the binder for functional layer is 100% by mass, the content ratio of the binder functional group-containing monomer unit in the binder for functional layer is preferably 20% by mass or more, more preferably 30% by mass or more, even more preferably 50% by mass or more, and particularly preferably 70% by mass or more, from the viewpoint of further improving the adhesiveness of the functional layer. Note that the upper limit of the content ratio of the binder functional group-containing monomer unit in the binder for functional layer is not particularly limited, and can be 100% by mass or less.

[0075] [Other repeating units] The binder for the functional layer may contain a repeating unit (other repeating unit) other than the above-mentioned binder functional group-containing monomer unit. Such other repeating units are not particularly limited, and may include repeating units listed in the section "Composite particles for electrochemical element functional layer" that do not correspond to the binder functional group-containing monomer unit. The binder for the functional layer may contain one type of other repeating unit, or may contain two or more types.

[0076] <<Method for preparing binder for functional layer>> In the present invention, the method for preparing the binder for the functional layer is not particularly limited. The binder for the functional layer is produced, for example, by polymerizing a monomer composition containing one or more types of monomers in an aqueous solvent, and optionally hydrogenating or modifying the monomer composition. The content ratio of each monomer in the monomer composition can be determined according to the content ratio of the desired monomer unit (repeating unit) in the polymer. The polymerization method is not particularly limited, and any method such as solution polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc. can be used. The polymerization reaction can be any reaction such as ionic polymerization, radical polymerization, living radical polymerization, various condensation polymerization, addition polymerization, etc. In addition, during polymerization, a known emulsifier or polymerization initiator can be used as necessary. Furthermore, hydrogenation and modification can be performed by known methods.

[0077] <<Types of binders for functional layers>> As the binder for the functional layer, from the viewpoint of further improving the adhesiveness of the functional layer, for example, polyacrylonitrile, polybutyl acetal (polyvinyl formal, polyvinyl butyral, etc.), polyvinylpyrrolidone, etc. can be preferably used, polyvinylpyrrolidone and polyacrylonitrile are more preferable, and polyacrylonitrile is even more preferable. As the binder for the functional layer, a known binder not having the above-mentioned binder functional group (such as polyvinylidene fluoride) can also be used.

[0078] <<Binder content for functional layer>> The binder composition of the present invention preferably contains 30 parts by mass or more of the binder for the functional layer (particularly the binder for the functional layer having the binder functional group described above) per 100 parts by mass of the composite particles described above, more preferably 40 parts by mass or more, even more preferably 50 parts by mass or more, preferably 2000 parts by mass or less, more preferably 400 parts by mass or less, and even more preferably 250 parts by mass or less. When preparing the binder composition, by blending 30 parts by mass or more of the binder for the functional layer per 100 parts by mass of the composite particles, the adhesiveness of the functional layer can be further improved while further improving the high-temperature storage characteristics of the electrochemical element, and by blending 2000 parts by mass or less of the binder for the functional layer, an electrochemical element with sufficient safety can be obtained.

[0079] <Other ingredients> Furthermore, in addition to the above-mentioned components, the binder composition of the present invention may contain known components such as a crosslinking agent, a reinforcing agent, an antioxidant, a dispersant, a rheology modifier, an electrolyte additive having a function of suppressing decomposition of the electrolyte, etc. Furthermore, as the other components, one type may be contained, or two or more types may be contained in any ratio.

[0080] <Method of preparing binder composition> The binder composition of the present invention can be prepared by mixing the composite particles and a solvent, as well as the binder for the functional layer used as needed and other components. Specifically, the binder composition can be prepared by dissolving and / or dispersing the composite particles, as well as the binder for the functional layer used as needed and other components in a solvent. Here, when preparing the binder composition, it is preferable that the binder for the functional layer is mixed with the composite particles in a state where it is dissolved in a solvent. In obtaining the binder composition, there is no particular limitation on the mixing method, and for example, a general mixing device such as a disperser, a mill, or a kneader can be used. The binder composition may be prepared simultaneously with the preparation of the conductive paste for the electrode mixture layer, which will be described later.

[0081] (Conductive paste for electrode composite layer) The conductive material paste of the present invention is a composition containing the binder composition of the present invention described above and a conductive material. That is, the conductive material paste of the present invention contains the composite particles, the solvent, and a conductive material, and may optionally contain the functional layer binder and other components described above. Note that the conductive material paste of the present invention does not usually contain electrode active material particles. Furthermore, by using the conductive material paste of the present invention, an electrode mixture layer having excellent adhesiveness can be formed, and by using an electrode having this electrode mixture layer, an electrochemical element having sufficient safety and excellent high-temperature storage characteristics can be manufactured.

[0082] <Conductive material> The conductive material is for increasing the conductivity of the electrode mixture layer of the electrode for electrochemical elements in the electrochemical element. Here, the conductive material is not particularly limited, and conductive carbon materials and fibers, foils, or particles of various metals can be used. Examples of the conductive carbon material include carbon black (e.g., acetylene black, Ketjen Black (registered trademark), furnace black, etc.), single-walled or multi-walled carbon nanotubes (multi-walled carbon nanotubes include cup-stack type), carbon nanohorns, vapor-grown carbon fibers, milled carbon fibers obtained by crushing polymer fibers after firing, single-layered or multi-layered graphene, and carbon nonwoven fabric sheets obtained by firing nonwoven fabrics made of polymer fibers. The conductive material may be used alone or in combination of two or more kinds in any ratio.

[0083] The conductive material has a specific surface area of ​​30m 2 / g or more, and 2 / g or more is more preferable, and 2,000m 2 / g or less, and 1,500m 2 / g or less is more preferable, and 1,000m 2 / g or less is more preferable, 2 It is particularly preferable that the specific surface area of ​​the conductive material is 30 m 2 / g or more, an electrode mixture layer with excellent conductivity can be formed even when the content of the conductive material is small. 2 / g or less, the dispersibility of the conductive material can be improved. In the present invention, the specific surface area of ​​the conductive material refers to a nitrogen adsorption specific surface area measured using a BET method, and can be measured in accordance with ASTM D3037-81.

[0084] The conductive material paste of the present invention preferably contains 10 parts by mass or more of the conductive material per 100 parts by mass of the composite particles, more preferably 20 parts by mass or more, and even more preferably 30 parts by mass or more, and preferably 2000 parts by mass or less, more preferably 400 parts by mass or less, and even more preferably 350 parts by mass or less. When preparing the conductive material paste, by blending 10 parts by mass or more and 2000 parts by mass or less of the conductive material per 100 parts by mass of the composite particles, the conductive material can be well dispersed in the conductive material paste. Then, by using the conductive material paste, it is possible to form an electrode mixture layer that allows the electrochemical element to exhibit excellent element characteristics (such as rate characteristics) while fully ensuring the safety of the electrochemical element.

[0085] <Preparation method of conductive paste> The conductive paste of the present invention can be prepared by mixing the binder composition and the conductive material. There are no particular limitations on the mixing method for obtaining the conductive paste, and for example, a general mixing device such as a disper, a mill, or a kneader can be used. The solid content concentration of the conductive paste is preferably 3% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less.

[0086] (Slurry for electrode mixture layer) The electrode mixture layer slurry of the present invention is a composition containing the conductive material paste and electrode active material particles. That is, the electrode mixture layer slurry of the present invention contains electrode active material particles, the composite particles, the solvent, and the conductive material, and may optionally contain the functional layer binder and other components. Furthermore, by using the slurry for electrode mixture layer of the present invention, an electrode mixture layer having excellent adhesiveness can be formed, and by using an electrode having such an electrode mixture layer, an electrochemical element having sufficient safety and excellent high-temperature storage characteristics can be manufactured.

[0087] <Electrode active material particles> The electrode active material particles are particles composed of a material that transfers electrons at the electrode of an electrochemical element. And, for example, when the electrochemical element is a lithium-ion secondary battery, usually a material that can occlude and release lithium is used as the electrode active material.

[0088] In the following, as an example, the case where the slurry for the electrode mixture layer is the slurry for the electrode mixture layer of a lithium-ion secondary battery electrode will be described, but the present invention is not limited to the following example.

[0089] <<Positive electrode active material particles>> The positive electrode active material forming the positive electrode active material particles is not particularly limited, and includes lithium-containing cobalt oxide (LiCoO 2 ), lithium manganate (LiMn 2 O 4 ), lithium-containing nickel oxide (LiNiO 2 ), lithium-containing composite oxide of Co-Ni-Mn, lithium-containing composite oxide of Ni-Mn-Al, lithium-containing composite oxide of Ni-Co-Al, olivine-type lithium iron phosphate (LiFePO 4 ), olivine-type lithium manganese phosphate (LiMnPO 4 ), Li 1+x Mn 2-x O 4 (spinel compound with excess lithium represented by 0 <X <2), Li[Ni 0.17 Li 0.2 Co 0.07 Mn 0.56 O 2 , LiNi 0.5 Mn 1.5 O 4 etc. In addition, the particle diameter of the positive electrode active material particles is not particularly limited and can be the same as that of the conventionally used positive electrode active material particles.

[0090] <<Negative electrode active material particles>> The negative electrode active material forming the negative electrode active material particles is not particularly limited, and examples thereof include carbon-based negative electrode active materials, metal-based negative electrode active materials, and negative electrode active materials that are combinations of these. The particle size of the negative electrode active material particles is not particularly limited, and may be the same as that of conventionally used negative electrode active material particles.

[0091] [Carbon-based negative electrode active material] Here, the carbon-based negative electrode active material refers to an active material having carbon as the main skeleton into which lithium can be inserted (also referred to as "doped"). Examples of the carbon-based negative electrode active material include carbonaceous materials and graphite materials.

[0092] -Carbonaceous materials- Examples of the carbonaceous material include graphitic carbon and non-graphitic carbon having a structure close to an amorphous structure, such as glassy carbon. Here, examples of graphitizable carbon include carbon materials made from tar pitch obtained from petroleum or coal. Specific examples include coke, mesocarbon microbeads (MCMB), mesophase pitch-based carbon fiber, and pyrolytic vapor-grown carbon fiber. Examples of non-graphitizable carbon include phenol resin baked body, polyacrylonitrile carbon fiber, pseudoisotropic carbon, furfuryl alcohol resin baked body (PFA), and hard carbon.

[0093] -Graphite material- Furthermore, examples of the graphite material include natural graphite and artificial graphite. Examples of the artificial graphite include artificial graphite obtained by heat-treating carbon containing graphitizable carbon mainly at 2800° C. or higher, graphitized MCMB obtained by heat-treating MCMB at 2000° C. or higher, and graphitized mesophase pitch-based carbon fiber obtained by heat-treating mesophase pitch-based carbon fiber at 2000° C. or higher. In the present invention, natural graphite at least a part of the surface of which is coated with amorphous carbon (amorphous coated natural graphite) may be used as the carbon-based negative electrode active material.

[0094] [Metallic negative electrode active material] The metal-based negative electrode active material is an active material containing a metal, and usually refers to an active material that contains an element capable of inserting or alloying lithium in its structure, and has a theoretical current capacity of 500 mAh / g or more per unit mass when lithium is inserted or alloyed. Examples of the metal-based active material include lithium metal, elemental metals capable of forming lithium alloys (e.g., Ag, Al, Ba, Bi, Cu, Ga, Ge, In, Ni, P, Pb, Sb, Si, Sn, Sr, Zn, Ti, etc.), and alloys thereof, as well as oxides, sulfides, nitrides, silicides, carbides, and phosphides thereof. Among these, the metal-based negative electrode active material is preferably an active material containing silicon (silicon-based negative electrode active material). This is because the use of a silicon-based negative electrode active material can increase the capacity of a lithium-ion secondary battery.

[0095] - Silicon-based negative electrode active material - Examples of silicon-based negative electrode active materials include silicon (Si), alloys containing silicon, SiO, and SiO x and a composite of a Si-containing material and conductive carbon, which is obtained by coating a Si-containing material with conductive carbon or by forming a composite with the Si-containing material.

[0096] The ratio of the electrode active material particles and the composite particles in the electrode mixture layer slurry of the present invention is not particularly limited. For example, the electrode mixture layer slurry preferably contains 0.1 parts by mass or more of the composite particles per 100 parts by mass of the electrode active material particles, more preferably 0.5 parts by mass or more, more preferably 20 parts by mass or less, and more preferably 4 parts by mass or less. When preparing the electrode mixture layer slurry, if the conductive material paste is mixed in an amount such that the composite particles are 0.1 parts by mass or more per 100 parts by mass of the electrode active material particles, the safety of the electrochemical device can be further ensured, and if the conductive material paste is mixed in an amount such that the composite particles are 20 parts by mass or less per 100 parts by mass of the electrode active material particles, the device characteristics (e.g., rate characteristics) of the electrochemical device can be sufficiently ensured.

[0097] <Method of preparing slurry for electrode mixture layer> The electrode mixture layer slurry of the present invention can be prepared by mixing the conductive paste and the electrode active material particles. For mixing, a known mixer such as a ball mill, a sand mill, a bead mill, a pigment disperser, a crusher, an ultrasonic disperser, a homogenizer, a planetary mixer, or a Filmix mixer can be used.

[0098] (Electrodes for electrochemical elements) The electrode for electrochemical devices of the present invention comprises a current collector and an electrode mixture layer formed on the current collector, and the electrode mixture layer is a dried product of the electrode mixture layer slurry of the present invention. The electrode for electrochemical devices of the present invention may optionally comprise layers other than the electrode mixture layer (e.g., an adhesive layer or a porous membrane layer). The electrode for electrochemical devices of the present invention can be used as an electrode for electrochemical devices such as lithium ion secondary batteries, electric double layer capacitors, and lithium ion capacitors. Furthermore, by using the electrode of the present invention, an electrochemical element can be produced which is sufficiently safe and has excellent high-temperature storage characteristics.

[0099] <Current collector> The current collector of the electrode for electrochemical elements is not particularly limited as long as it is an electrically conductive and electrochemically durable material, and may be selected according to the type of electrochemical element. When the electrode for electrochemical elements is an electrode for a lithium ion secondary battery, the material constituting the current collector may be iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, platinum, etc. Among them, copper foil is particularly preferred as the current collector used for the negative electrode. Aluminum foil is particularly preferred as the material constituting the current collector used for the positive electrode. These materials may be used alone or in combination of two or more kinds in any ratio.

[0100] <Electrode composite layer> The electrode mixture layer formed by using the electrode mixture layer slurry of the present invention is a dried product of the electrode mixture layer slurry. Here, each component contained in the electrode mixture layer is the same as that contained in the slurry for the electrode mixture layer of the present invention, and the preferred abundance ratio of each of those components is the same as the preferred abundance ratio of each component in the slurry for the electrode mixture layer of the present invention.

[0101] <Method of manufacturing electrodes for electrochemical devices> Here, the manufacturing method of the electrode for electrochemical elements is not particularly limited, and for example, the electrode is manufactured through a step of applying a slurry for an electrode composite layer to at least one surface of a current collector (application step), and a step of drying the slurry for the electrode composite layer applied to at least one surface of the current collector to form an electrode composite layer on the current collector (drying step).

[0102] <<Coating process>> The method of applying the electrode mixture layer slurry onto the current collector is not particularly limited, and any known method can be used. Specifically, the application method can be a doctor blade method, a dip method, a reverse roll method, a direct roll method, a gravure method, an extrusion method, a brush coating method, or the like. The thickness of the slurry film on the current collector after application and before drying can be appropriately set according to the thickness of the electrode mixture layer obtained by drying.

[0103] <<Drying process>> The method for drying the slurry for the electrode mixture layer on the current collector is not particularly limited, and a known method can be used, for example, drying with warm air, hot air, or low-humidity air, vacuum drying, or drying by irradiation with infrared rays or electron beams, etc. By drying the slurry for the electrode mixture layer on the current collector in this manner, an electrode mixture layer can be formed on the current collector, and an electrode for an electrochemical element including the current collector and the electrode mixture layer can be obtained.

[0104] After the drying step, the electrode mixture layer may be subjected to a pressure treatment using a mold press or a roll press, etc. The pressure treatment can improve the adhesion between the electrode mixture layer and the current collector.

[0105] (Electrochemical element) The electrochemical element of the present invention is characterized by comprising the above-mentioned electrode for electrochemical element. The electrochemical element of the present invention is not particularly limited, and may be, for example, a lithium ion secondary battery, an electric double layer capacitor, or a lithium ion capacitor, and is preferably a lithium ion secondary battery. Since the electrochemical element of the present invention comprises the electrode of the present invention, thermal runaway is suppressed, high safety is maintained, and the high-temperature storage characteristics are also excellent.

[0106] Hereinafter, an example will be described in which the electrochemical element is a lithium ion secondary battery, but the present invention is not limited to the following example. A lithium ion secondary battery as the electrochemical element of the present invention usually comprises electrodes (positive and negative electrodes), an electrolyte, and a separator, and uses the electrochemical element electrode of the present invention for at least one of the positive and negative electrodes.

[0107] <Electrode> Here, the electrode other than the above-mentioned electrode for electrochemical elements of the present invention that can be used in the lithium ion secondary battery as the electrochemical element of the present invention is not particularly limited, and a known electrode can be used. Specifically, the electrode other than the above-mentioned electrode for electrochemical elements can be an electrode formed by forming an electrode mixture layer on a current collector using a known manufacturing method.

[0108] <Electrolyte> The electrolyte is usually an organic electrolyte in which a supporting electrolyte is dissolved in an organic solvent. For example, a lithium salt is used as the supporting electrolyte. For example, LiPF 6 , LiAsF 6 , LiBF 4 , LiSbF 6 , LiAlCl 4 , LiClO 4 , C.F. 3 SO 3 Li, C. 4 F 9 SO 3 Li, C.F. 3 COOLi, (CF 3 CO) 2NLi, (CF 3 SO 2 ) 2 NLi, (C 2 F 5 SO 2 Among them, LiPF is the most popular because it is easily soluble in solvents and has a high degree of dissociation. 6 , LiClO 4 , C.F. 3 SO 3 Li is preferred, and LiPF 6 is particularly preferred. The electrolyte may be used alone or in any combination of two or more kinds in any ratio. Usually, the lithium ion conductivity tends to increase as the supporting electrolyte with a higher degree of dissociation is used, so the lithium ion conductivity can be adjusted by the type of supporting electrolyte.

[0109] The organic solvent used in the electrolytic solution is not particularly limited as long as it can dissolve the supporting electrolyte, but for example, carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC), methyl ethyl carbonate (EMC), etc.; esters such as γ-butyrolactone and methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; sulfur-containing compounds such as sulfolane and dimethyl sulfoxide; etc. are preferably used. A mixture of these solvents may also be used. Among them, it is preferable to use carbonates because they have a high dielectric constant and a wide stable potential range, and it is more preferable to use a mixture of ethylene carbonate and ethyl methyl carbonate. The concentration of the electrolyte in the electrolytic solution can be appropriately adjusted, and is preferably 0.5 to 15 mass%, more preferably 2 to 13 mass%, and even more preferably 5 to 10 mass%. The electrolytic solution may contain known additives, such as vinylene carbonate, fluoroethylene carbonate, and ethyl methyl sulfone.

[0110] <separator> The separator is not particularly limited, and for example, the one described in JP 2012-204303 A can be used. Among these, a microporous film made of a polyolefin resin (polyethylene, polypropylene, polybutene, polyvinyl chloride) is preferred because it can reduce the thickness of the entire separator, thereby increasing the ratio of electrode active material particles in the lithium ion secondary battery and increasing the capacity per volume. Furthermore, as the separator, a separator with a functional layer, in which a functional layer (porous membrane layer or adhesive layer) is provided on one or both sides of a separator substrate, may be used.

[0111] In the present invention, known binders and non-conductive particles (for example, non-conductive inorganic particles such as alumina) can be used to form the functional layer of the separator with a functional layer. In the present invention, a binder composition containing the composite particles of the present invention can also be used to form the functional layer of the separator with the functional layer.

[0112] <Method of manufacturing lithium-ion secondary battery> The lithium ion secondary battery according to the present invention can be produced, for example, by stacking a positive electrode and a negative electrode with a separator therebetween, wrapping or folding the stack according to the battery shape as necessary, placing the stack in a battery container, injecting an electrolyte into the battery container, and sealing the container. In order to prevent the occurrence of an internal pressure rise in the secondary battery, overcharging and discharging, etc., a fuse, an overcurrent prevention element such as a PTC element, an expanded metal, a lead plate, etc. may be provided as necessary. The shape of the secondary battery may be, for example, any of a coin type, a button type, a sheet type, a cylindrical type, a square type, a flat type, etc. EXAMPLES

[0113] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples. In the following description, "%" and "parts" expressing amounts are based on mass unless otherwise specified. In addition, in a polymer produced by copolymerizing multiple types of monomers, the ratio of monomer units formed by polymerizing a certain monomer in the polymer usually coincides with the ratio (feed ratio) of that certain monomer to all monomers used in the polymerization of the polymer, unless otherwise specified. In the examples and comparative examples, the electrolyte swelling degree of the shell polymer, the thermal decomposition onset temperature of the composite particles, the adhesion of the positive electrode composite layer (functional layer), and the safety and high-temperature storage characteristics of the lithium ion secondary battery (electrochemical element) were measured or evaluated using the following methods.

[0114] <Electrolyte swelling rate> The aqueous dispersion of the shell polymer was applied onto a polytetrafluoroethylene sheet and dried for 3 to 8 hours in an environment at a temperature of 80 to 120°C to obtain a cast film with a thickness of 500 μm ± 50 μm. This cast film was cut and approximately 1 g was precisely weighed. The mass of the obtained film piece was designated as W0. This film piece was immersed in a measurement electrolyte for 72 hours in an environment at a temperature of 60°C to cause it to swell. The measurement electrolyte was a mixed solvent obtained by mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a mass ratio of EC / DEC = 3 / 7, and further adding 2 vol% of vinylene carbonate as an additive, to the resulting mixed solvent, and LiPF 6 A solution of 1.0 mol / L of the electrolyte was used. The film piece was then pulled out, the electrolyte on the surface was lightly wiped off, and the mass was measured. The mass of the film piece after swelling was designated as W1, and the electrolyte swelling degree was calculated using the following formula. Electrolyte swelling rate (mass%) = {(W1-W0) / W0} x 100 In Tables 1 and 2 described later, the degree of swelling in the electrolyte is expressed by the following ranks A to D. A: Electrolyte swelling degree is 100% by mass or more and 300% by mass or less B: Electrolyte swelling degree is more than 300% by mass and less than 400% by mass C: Electrolyte swelling degree is more than 400% by mass and less than 500% by mass D: Electrolyte swelling degree exceeds 500% by mass <Thermal decomposition start temperature> In thermogravimetric analysis using a thermogravimetric analyzer (manufactured by Rigaku, product name "TG8110"), the mass was measured while the temperature was raised from 25°C to 500°C at a heating rate of 20°C / min in an air atmosphere, and the temperature at which the measured mass was 95% of the mass at the start of the measurement (25°C) (i.e., the 5% mass reduction temperature) was defined as the thermal decomposition starting temperature of the composite particles. <Adhesiveness> The positive electrodes for lithium ion secondary batteries prepared in the Examples and Comparative Examples were cut into rectangles with a length of 100 mm and a width of 10 mm to prepare test pieces, and the surface of the positive electrode composite layer of the test pieces was attached to a test stand (SUS substrate) via cellophane tape (compliant with JIS Z1522) with the surface having the positive electrode composite layer facing down. Thereafter, one end of the current collector was pulled in the vertical direction at a pulling speed of 50 mm / min and peeled off, and the stress (N / m) was measured (note that the cellophane tape was fixed to the test stand). The same measurement as above was carried out three times, and the average value was calculated as the positive electrode peel strength, which was then evaluated according to the following criteria. A larger positive electrode peel strength value indicates that the positive electrode mixture layer has better adhesiveness and is more firmly attached to the current collector. <<Evaluation Criteria>> SA: Positive electrode peel strength is 35N / m or more A: Positive electrode peel strength is 30N / m or more and less than 35N / m B: Positive electrode peel strength is 25N / m or more and less than 30N / m C: Positive electrode peel strength is 20N / m or more and less than 25N / m D: Positive electrode peel strength is less than 20N / m <Safety> The safety of the lithium ion secondary battery was evaluated by the following internal short circuit test. The separator with porous membrane layer obtained as described below (substrate = polypropylene, porous membrane layer thickness 4 μm, 1 cm square hole) was sandwiched between the positive electrode for lithium ion secondary battery and the negative electrode for lithium ion secondary battery prepared in the examples and comparative examples (each with a tab), and the member was sealed with an aluminum pouch to prepare a cell. A forced internal short circuit was prepared by applying a force of 10 N to the holed part of the separator with porous membrane layer of the cell with a cylinder (SUS) of 8 mm diameter. 10 V was applied to the positive electrode tab and the negative electrode tab of the cell using a DC stabilized power supply (manufactured by Kikusui Electronics Co., Ltd., product name "PWR1201L"), and the current and voltage at that time were monitored. The resistance was calculated from the current and voltage, and the time at which the resistance became 100 times (resistance 100 times time) was measured immediately after applying a voltage of 10 V. Then, it was evaluated according to the following criteria. <<Evaluation Criteria>> A: Resistance 100 times for less than 5 seconds B: 100x resistance for 5 seconds or more but less than 10 seconds C: 100x resistance for 10 seconds or more but less than 15 seconds D: Resistance 100x for 15 seconds or more <<Preparation of separator with porous membrane layer>> As a separator substrate, a single-layer polypropylene separator (manufactured by Celgard, product name "#2500") was prepared. A composition for a porous membrane layer was prepared by mixing 100 parts of alumina filler (manufactured by Nippon Light Metal Co., Ltd., "LS256") as a non-conductive particle with 6.0 parts of an acrylic polymer as a binder in terms of solid content, 1.5 parts of an acrylamide polymer with a carboxylic acid group introduced therein as a thickener (manufactured by Arakawa Chemical Co., Ltd., "Polystron (registered trademark) 117") in terms of solid content, and 0.2 parts of a polyethylene glycol type surfactant (manufactured by San Nopco Ltd., "San Nopco (registered trademark) SN Wet 366") in terms of solid content. The porous membrane layer composition obtained as described above was applied to one side of the separator substrate using a wire bar, and dried for 10 minutes at 60° C. This resulted in a separator with a porous membrane layer having a thickness of 4 μm. <High temperature storage characteristics> After injecting the electrolyte, the lithium ion secondary battery was left to stand at 25°C for 5 hours. Next, the battery was charged to a cell voltage of 3.65V at 25°C by a constant current method of 0.2C, and then aged at 60°C for 12 hours. Then, the battery was discharged to a cell voltage of 3.00V at 25°C by a constant current method of 0.2C. Then, the battery was CC-CV charged (upper cell voltage 4.20V) at a constant current method of 0.2C, and CC discharged to 3.00V at a constant current method of 0.2C. This charge and discharge at 0.2C was repeated three times. The discharge capacity obtained at the last charge and discharge was designated as X1. Thereafter, the cell was charged at 25° C. up to a cell voltage of 4.20 V, and then left for 2 weeks in an environment at a temperature of 60° C. Thereafter, the cell was discharged at 25° C. by a constant current method of 0.2 C down to a cell voltage of 3.00 V. The discharge capacity was designated as X2. The discharge capacity X1 and the discharge capacity X2 were used to calculate the capacity retention rate represented by ΔC=(X2 / X1)×100(%), and the capacity retention rate was evaluated according to the following criteria: A larger capacity retention rate ΔC indicates better high-temperature storage characteristics. <<Evaluation Criteria>> A: ΔC is 85% or more B: ΔC is 83% or more and less than 85% C: ΔC is 80% or more but less than 83% D: ΔC is less than 80%

[0115] Example 1 <Preparation of core material> As a core material for forming the core particles, melamine cyanurate was prepared. <Preparation of shell polymer (polymer A)> In a reactor A equipped with a mechanical stirrer and a condenser, 85 parts of ion-exchanged water and 0.2 parts of sodium dodecylbenzenesulfonate were placed under a nitrogen atmosphere, and then heated to 55°C while stirring, and 0.3 parts of potassium persulfate was added to the reactor A as a 5.0% aqueous solution. Next, in another vessel B equipped with a mechanical stirrer, 94.0 parts of acrylonitrile as a nitrile group-containing monomer, 1.0 parts of acrylamide as an amide group-containing monomer, 2.0 parts of acrylic acid as a carboxylic acid group-containing monomer, and 3.0 parts of n-butyl acrylate as a (meth)acrylic acid ester monomer unit, as well as 0.6 parts of sodium dodecylbenzenesulfonate, 0.035 parts of t-dodecyl mercaptan, 0.4 parts of polyoxyethylene lauryl ether, and 80 parts of ion-exchanged water were added under a nitrogen atmosphere, and the mixture was emulsified by stirring to prepare a monomer mixture. Then, this monomer mixture was added to reactor A at a constant rate over 5 hours while being stirred and emulsified, and the reaction was continued until the polymerization conversion rate reached 95%, to obtain an aqueous dispersion of a shell polymer (shell material) which was polyacrylonitrile. The swelling degree of this shell polymer in the electrolyte was measured. The results are shown in Table 1. <Preparation of composite particles> The solids concentration of the aqueous dispersion of the shell polymer obtained above was adjusted to give an aqueous dispersion with a solids concentration of 28%. To a homomixer, 80 parts of the above melamine cyanurate as a core material and 20 parts (solids equivalent) of the aqueous dispersion of the above shell polymer after adjusting the solid content were added, and the total solid content was adjusted to 20% with ion-exchanged water, followed by stirring and mixing to obtain a slurry composition. The obtained slurry composition was supplied to a spray dryer (manufactured by Okawara Kakoki Co., Ltd., product name "OC-16") and spray-dried using a rotating disk type atomizer (diameter 65 mm) under conditions of a rotation speed of 25,000 rpm, a hot air temperature of 150°C, and a particle recovery outlet temperature of 90°C, to obtain composite particles. The composite particles were observed using a scanning electron microscope (SEM), and it was confirmed that the entire outer surface of the core particle was covered with a shell polymer. The thermal decomposition onset temperature of the composite particles was also measured. The results are shown in Table 1. <Preparation of binder for functional layer> In the same manner as in "Preparation of shell polymer", an aqueous dispersion of a functional layer binder, which is polyacrylonitrile (polymer A), was obtained. An appropriate amount of NMP was added to the obtained aqueous dispersion of the functional layer binder (polymer A) to obtain a mixture. Then, water and excess NMP were removed from the mixture by vacuum distillation at 90°C, and an NMP solution (solid content concentration: 8%) of the functional layer binder (polymer A) was obtained. <Preparation of conductive paste> In a dry room with a dew point of -40°C, acetylene black (BET specific surface area: 68 m) was used as a conductive material. 2 100 parts of 100 parts of 100% by weight of the mixture (100 parts by weight / g), 40 parts of the composite particles obtained as described above, 40 parts of the binder for the functional layer in terms of solid content, and an appropriate amount of NMP as a solvent were stirred with a disperser (3000 rpm, 60 minutes), and then mixed for 1 hour at a peripheral speed of 8 m / sec using a bead mill using zirconia beads with a diameter of 0.3 mm, to prepare a conductive material paste. The solid content concentration of the conductive material paste was 15.0 mass%. Furthermore, by this operation, a binder composition and a conductive material paste were simultaneously prepared. <Preparation of slurry for positive electrode mixture layer> The planetary mixer was fitted with Co-Ni-Mn lithium composite oxide active material NMC532 (LiNi 0.5 Mn 0.3 Co 0.2 O 2 100 parts of the conductive paste prepared above, 3.75 parts in terms of solids, and 2.0 parts in terms of solids of polyvinylidene fluoride (PVDF) (manufactured by Kureha Chemical Industry, product name "L#7208") as a known binder having no binder functional groups were mixed, and NMP was gradually added thereto, and the mixture was stirred and mixed at a temperature of 25±3°C and a rotation speed of 60 rpm. A slurry for a positive electrode mixture layer was obtained by adjusting the viscosity to 3,600 mPa s at 25±3°C using a B-type viscometer at 60 rpm (rotor M4). <Production of positive electrodes> The slurry for the positive electrode mixture layer obtained as described above was applied to a 20 μm-thick aluminum foil current collector with a comma coater in an amount of 20±0.5 mg / cm. 2 The coating was applied so that the result was as follows. The positive electrode composite layer slurry on the aluminum foil was dried by transporting the aluminum foil at a speed of 200 mm / min through an oven at a temperature of 90° C. for 2 minutes and then through an oven at a temperature of 120° C. for 2 minutes, thereby obtaining a positive electrode raw sheet in which a positive electrode composite layer was formed on the current collector. Thereafter, the positive electrode composite layer side of the prepared positive electrode blank was roll-pressed under conditions of a temperature of 25±3°C and a linear pressure of 14 tonnes, so that the density of the positive electrode composite layer became 3.20 g / cm 3 The positive electrode was obtained. The adhesiveness of the positive electrode mixture layer was evaluated for the obtained positive electrode. Furthermore, the safety of the lithium ion secondary battery was evaluated using the obtained positive electrode and the negative electrode described later. The results are shown in Table 1.

[0116] <Production of negative electrodes> In a 5 MPa pressure vessel equipped with a stirrer, 63 parts of styrene as an aromatic vinyl monomer, 34 parts of 1,3-butadiene as an aliphatic conjugated diene monomer, 2 parts of itaconic acid as a carboxylic acid group-containing monomer, 1 part of 2-hydroxyethyl acrylate as a hydroxyl group-containing monomer, 0.3 parts of t-dodecyl mercaptan as a molecular weight regulator, 5 parts of sodium dodecylbenzenesulfonate as an emulsifier, 150 parts of ion-exchanged water as a solvent, and 1 part of potassium persulfate as a polymerization initiator were added, thoroughly stirred, and then heated to a temperature of 55 ° C. to start polymerization. When the monomer consumption reached 95.0%, the reaction was stopped by cooling. A 5% aqueous sodium hydroxide solution was added to the aqueous dispersion containing the polymer obtained in this way to adjust the pH to 8. Thereafter, unreacted monomers were removed by heating and reduced pressure distillation. Thereafter, the temperature was cooled to 30 ° C. or less to obtain an aqueous dispersion containing a binder for a negative electrode (a binder composition for a negative electrode). Into a planetary mixer, 48.75 parts of artificial graphite (theoretical capacity: 360mAh / g) as negative electrode active material particles, 48.75 parts of natural graphite (theoretical capacity: 360mAh / g), and 1 part of carboxymethylcellulose as a thickener in terms of solid content were added. Further, the mixture was diluted with ion-exchanged water so that the solid content concentration was 60%, and then kneaded for 60 minutes at a rotation speed of 45 rpm. Then, 1.5 parts of the negative electrode binder composition obtained above in terms of solid content were added, and kneaded for 40 minutes at a rotation speed of 40 rpm. Then, ion-exchanged water was added so that the viscosity was 3000±500mPa·s (measured with a B-type viscometer at 25°C and 60 rpm), to prepare a negative electrode slurry composition. The negative electrode slurry composition was applied to the surface of a 15 μm-thick copper foil current collector with a comma coater in an amount of 11±0.5 mg / cm 2 Thereafter, the copper foil coated with the negative electrode slurry composition was transported at a speed of 400 mm / min through an oven at a temperature of 80° C. for 2 minutes and then through an oven at a temperature of 110° C. for 2 minutes, thereby drying the negative electrode slurry composition on the copper foil and obtaining a negative electrode raw sheet having a negative electrode mixture layer formed on a current collector. Thereafter, the negative electrode composite layer side of the produced negative electrode blank was roll-pressed under conditions of a temperature of 25±3°C and a linear pressure of 11 t (tons) to obtain a negative electrode composite layer density of 1.60 g / cm 3 A negative electrode of 1000 nm was obtained.

[0117] <Preparing the separator> A single-layer polypropylene separator (manufactured by Celgard, product name "#2500") was prepared.

[0118] <Production of lithium-ion secondary battery> A single-layer laminate cell (with an initial design discharge capacity of 30 mAh) was fabricated using the above positive and negative electrodes and a separator, and placed in an aluminum package. Then, 1.0 M LiPF was added as the electrolyte. 6A solution (solvent: mixed solvent of ethylene carbonate (EC) / diethyl carbonate (DEC) = 3 / 7 (mass ratio), additive: containing 2 volume % (solvent ratio) of vinylene carbonate) was filled in. Furthermore, in order to seal the opening of the aluminum packaging material, the aluminum packaging material was closed by heat sealing at a temperature of 150°C, and a lithium ion secondary battery was produced. The high-temperature storage characteristics of the obtained lithium ion secondary battery were evaluated. The results are shown in Table 1.

[0119] Example 2 In preparing the composite particles, except that the shell polymer prepared as follows was used, the composite particles, the binder for the functional layer (polymer A), the conductive paste, the slurry for the positive electrode composite layer, the positive electrode, the negative electrode, the separator, and the lithium ion secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 1. <Preparation of Shell Polymer (Polymer B)> In an autoclave equipped with a stirrer, 240 parts of ion-exchanged water, 2.5 parts of sodium alkylbenzenesulfonate, 20 parts of acrylonitrile as a nitrile group-containing monomer, 10 parts of styrene as an aromatic vinyl monomer, and 5 parts of methacrylic acid as a carboxylic acid group-containing monomer were placed in this order, and the inside of the bottle was replaced with nitrogen. Then, 65 parts of 1,3-butadiene as an aliphatic conjugated diene monomer was pressed in, and 0.25 parts of ammonium persulfate was added, and polymerization reaction was carried out at a reaction temperature of 40°C. Then, a polymer containing acrylonitrile units, styrene units, methacrylic acid units, and 1,3-butadiene units was obtained. The polymerization conversion rate was 85%, and the iodine value was 280mg / 100mg. The total solids concentration of the obtained polymer was adjusted to 12% using water, and 400 mL (total solids content 48 g) of the solution was added to a 1 L autoclave equipped with a stirrer. After removing the dissolved oxygen in the solution by flowing nitrogen gas for 10 minutes, 75 mg of palladium acetate as a catalyst for hydrogenation reaction was dissolved in 180 mL of ion-exchanged water to which nitric acid was added in an amount four times the moles of Pd, and added. After replacing the inside of the system twice with hydrogen gas, the contents of the autoclave were heated to 50°C while pressurizing with hydrogen gas up to 3 MPa, and hydrogenation reaction (first stage hydrogenation reaction) was carried out for 6 hours. At this time, the iodine value of the polymer was 45 mg / 100 mg. Next, the autoclave was returned to atmospheric pressure, and 25 mg of palladium acetate was dissolved in 60 mL of water containing 4 times the molar amount of nitric acid relative to Pd as a hydrogenation catalyst and added. After replacing the inside of the system with hydrogen gas twice, the contents of the autoclave were heated to 50°C while pressurized with hydrogen gas up to 3 MPa, and hydrogenation reaction (second stage hydrogenation reaction) was carried out for 6 hours to obtain an aqueous dispersion of a shell polymer (shell material) containing acrylonitrile units, styrene units, methacrylic acid units, and 1,3-butadiene hydride units.

[0120] Example 3 In preparing the composite particles, except that polyvinylpyrrolidone (Wako Pure Chemical Industries, special grade reagent, product name "Polyvinylpyrrolidone K30", polymer C) was used as the shell polymer, the composite particles, the binder for the functional layer (polymer A), the conductive paste, the slurry for the positive electrode mixture layer, the positive electrode, the negative electrode, the separator, and the lithium ion secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 1.

[0121] Example 4 In preparing the composite particles, except that the shell polymer prepared as follows was used, the composite particles, the binder for the functional layer (polymer A), the conductive paste, the slurry for the positive electrode composite layer, the positive electrode, the negative electrode, the separator, and the lithium ion secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 1. <Preparation of Shell Polymer (Polymer D)> 720 parts of ion-exchanged water was put into a 1L flask with a septum, heated to a temperature of 40°C, and the flask was replaced with nitrogen gas at a flow rate of 100mL / min. Next, 10 parts of ion-exchanged water, 30 parts of acrylic acid as a carboxylic acid group-containing monomer, and 70 parts of acrylamide as an amide group-containing monomer were mixed and injected into the flask with a syringe. Then, 8 parts of a 2.5% aqueous solution of potassium persulfate as a polymerization initiator were added into the flask with a syringe. Furthermore, 15 minutes later, 22 parts of a 2.0% aqueous solution of tetramethylethylenediamine as a polymerization promoter were added with a syringe. After 4 hours, 4 parts of a 2.5% aqueous solution of potassium persulfate as a polymerization initiator were added into the flask, and 11 parts of a 2.0% aqueous solution of tetramethylethylenediamine as a polymerization promoter were added, and the temperature was raised to 60°C to proceed with the polymerization reaction. After 3 hours, the flask was opened to the air to stop the polymerization reaction, and the product was deodorized at a temperature of 80°C to remove residual monomers. The pH of the product was then adjusted to 8 using a 10% aqueous solution of lithium hydroxide to obtain an aqueous dispersion of a shell polymer (shell material), which is an acrylic acid-acrylamide copolymer.

[0122] Example 5 In preparing the composite particles, the amount of melamine cyanurate was changed to 97 parts, and the amount of the solid content of the shell polymer was changed to 3 parts, but the composite particles, the binder for the functional layer (polymer A), the conductive paste, the slurry for the positive electrode mixture layer, the positive electrode, the negative electrode, the separator, and the lithium ion secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 1. The composite particles were observed with a scanning electron microscope (SEM) and it was confirmed that a part of the outer surface of the core particle was covered with the shell polymer.

[0123] Example 6 In preparing the composite particles, except that ammeline was used instead of melamine cyanurate, the composite particles, the binder for the functional layer (polymer A), the conductive paste, the slurry for the positive electrode composite layer, the positive electrode, the negative electrode, the separator, and the lithium ion secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 1. The composite particles were observed with a scanning electron microscope (SEM) and it was confirmed that a part of the outer surface of the core particle was covered with the shell polymer.

[0124] Example 7 Except for preparing the conductive paste as follows, the composite particles, the binder for the functional layer (polymer A), the slurry for the positive electrode composite layer, the positive electrode, the negative electrode, the separator, and the lithium ion secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 1. <Preparation of conductive paste> In a dry room with a dew point of -40°C, acetylene black (BET specific surface area: 68 m) was used as a conductive material. 2 A conductive paste was prepared by adding 100 parts of a 100% aqueous cellulose acetate solution (100 parts by weight / g), 60 parts of composite particles obtained in the same manner as in Example 1, 20 parts of a binder for functional layers (polymer A) obtained in the same manner as in Example 1 in terms of solid content, and NMP as an organic solvent, and stirring with a disperser (3000 rpm, 60 minutes), and then mixing for 1 hour at a peripheral speed of 8 m / sec using a bead mill using zirconia beads with a diameter of 0.3 mm. The solid content concentration of the conductive paste was 15.0 mass%.

[0125] Example 8 In preparing the conductive paste, polyvinylpyrrolidone (Wako Pure Chemical Industries, special grade reagent, product name "Polyvinylpyrrolidone K30", polymer C) was used instead of polyacrylonitrile (polymer A) as the binder for the functional layer. Except for this, the composite particles, conductive paste, slurry for the positive electrode composite layer, positive electrode, negative electrode, separator, and lithium ion secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 1.

[0126] Example 9 In preparing the composite particles, except that the shell polymer prepared as follows was used, the composite particles, the binder for the functional layer (polymer A), the conductive paste, the slurry for the positive electrode composite layer, the positive electrode, the negative electrode, the separator, and the lithium ion secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 2. <Preparation of Shell Polymer (Polymer E)> 76g of deionized water was charged into a 500ml glass separable flask equipped with a paddle impeller (SUS316 paddle-type rotor) stirrer, a reflux condenser, and four dropping devices, and the temperature was raised to the boiling reflux temperature. Next, while stirring, 166.04g of a mixture of 159.28g of 37% aqueous solution of sodium acrylate and 6.76g of 80% aqueous solution of acrylic acid, 81.9g of 40% aqueous solution of sodium 3-allyloxy-2-hydroxypropanesulfonate, 26.6g of 10% aqueous solution of sodium persulfate, and 44.5g of 2% aqueous solution of hydrogen peroxide were dropped separately, over 140 minutes for the mixture of the aqueous solution of sodium acrylate and the aqueous solution of acrylic acid, 120 minutes for the aqueous solution of sodium 3-allyloxy-2-hydroxypropanesulfonate, 160 minutes for the aqueous solution of sodium persulfate, and 140 minutes for the aqueous solution of hydrogen peroxide. After the dropwise addition was completed, the boiling reflux temperature was maintained for 30 minutes to complete the polymerization, and a pale yellow, transparent aqueous solution of a water-soluble copolymer (acrylic acid-sulfonic acid copolymer, shell material) was obtained.

[0127] Example 10 Except for preparing the composite particles as follows, the shell polymer (polymer E), the binder for the functional layer (polymer A), the conductive paste, the slurry for the positive electrode composite layer, the positive electrode, the negative electrode, the separator, and the lithium ion secondary battery were prepared in the same manner as in Example 9, and various evaluations were performed. The results are shown in Table 2. <Preparation of composite particles> The solids concentration of the aqueous solution of the shell polymer (Polymer E) was adjusted to give an aqueous solution with a solids concentration of 50%. Melamine cyanurate (80 parts) was fed as a core material into a dry mixer (FM mixer, manufactured by Nippon Coke & Co., Ltd.) and stirred at a peripheral speed of 40 m / sec. While stirring the melamine cyanurate, 20 parts (solid content equivalent) of the aqueous solution of the polymer E was sprayed into the dry mixer over 30 minutes to obtain composite particles. The composite particles were observed using a scanning electron microscope (SEM) and it was confirmed that the entire outer surface of the core particles was covered with the shell polymer.

[0128] Example 11 Except for preparing the composite particles as follows, the shell polymer (polymer E), the binder for the functional layer (polymer A), the conductive paste, the slurry for the positive electrode composite layer, the positive electrode, the negative electrode, the separator, and the lithium ion secondary battery were prepared in the same manner as in Example 9, and various evaluations were performed. The results are shown in Table 2. <Preparation of composite particles> The solids concentration of the aqueous solution of the shell polymer (Polymer E) was adjusted to give an aqueous solution with a solids concentration of 50%. 80 parts of melamine cyanurate as a core material was fed into a fluidized bed granulator (Agromaster (registered trademark), manufactured by Hosokawa Micron Corporation) and fluidized in an air current at 80°C. While fluidizing the melamine cyanurate, 20 parts (solid content equivalent) of the aqueous solution of the polymer E was sprayed into the fluidized bed granulator over 30 minutes to obtain composite particles. The composite particles were observed using a scanning electron microscope (SEM) and it was confirmed that the entire outer surface of the core particles was covered with the shell polymer.

[0129] Comparative Example 1 Except for not preparing the shell polymer and the composite particles, and preparing the conductive paste as follows, the binder for the functional layer (polymer A), the slurry for the positive electrode composite layer, the positive electrode, the negative electrode, the separator, and the lithium ion secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 2. <Preparation of conductive paste> In a dry room with a dew point of -40°C, acetylene black (BET specific surface area: 68 m) was used as a conductive material. 2 A conductive paste was prepared by adding 100 parts of 1,000g / g of melamine cyanurate, 40 parts of a binder for functional layers (polymer A) obtained in the same manner as in Example 1 in terms of solid content, and NMP as an organic solvent, and stirring with a disperser (3000 rpm, 60 minutes), and then mixing for 1 hour at a peripheral speed of 8 m / sec using a bead mill using zirconia beads with a diameter of 0.3 mm. The solid content concentration of the conductive paste was 15.0 mass%.

[0130] Comparative Example 2 Except for not preparing the shell polymer and the composite particles, and preparing the conductive paste and the slurry for the positive electrode composite layer as described below, the binder for the functional layer (polymer A), the positive electrode, the negative electrode, the separator, and the lithium ion secondary battery were prepared and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 2. <Preparation of conductive paste> It was prepared in the same manner as in Comparative Example 1. <Preparation of slurry for positive electrode mixture layer> The planetary mixer was fitted with Co-Ni-Mn lithium composite oxide active material NMC532 (LiNi 0.5 Mn 0.3 Co 0.2 O 2 100 parts of the conductive paste prepared above, 3.75 parts in terms of solids, 2.0 parts in terms of solids of polyvinylidene fluoride (PVDF) (manufactured by Kureha Chemical Industry, product name "L#7208") as a known binder having no binder functional groups, and 0.2 parts in terms of solids of Polymer A were mixed, and NMP was gradually added thereto, and the mixture was stirred and mixed at a temperature of 25±3°C and a rotation speed of 60 rpm. A slurry for a positive electrode mixture layer was obtained by adjusting the viscosity to 3,600 mPa s at 25±3°C using a B-type viscometer at 60 rpm (rotor M4).

[0131] (Comparative Examples 3 to 4) Except for using azobisisobutyronitrile (Comparative Example 3) and azodicarbonamide (Comparative Example 4) instead of melamine cyanurate in the preparation of the composite particles, the composite particles, the conductive paste, the slurry for the positive electrode mixture layer, the positive electrode, the negative electrode, the separator, and the lithium ion secondary battery were prepared and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0132] In addition, in the following Tables 1 and 2, "MC" indicates melamine cyanurate, "AM" stands for ammeline; "AIBN" refers to azobisisobutyronitrile; "ADCA" stands for azodicarbonamide, "Polymer A" refers to polyacrylonitrile, "Polymer B" refers to a polymer containing acrylonitrile units, styrene units, methacrylic acid units, and 1,3-butadiene hydride units; "Polymer C" represents polyvinylpyrrolidone, "Polymer D" represents an acrylic acid-acrylamide copolymer, "Polymer E" refers to an acrylic acid-sulfonic acid copolymer, "PVDF" refers to polyvinylidene fluoride.

[0133] [Table 1]

[0134] [Table 2]

[0135] As can be seen from Tables 1 and 2, in Examples 1 to 11 in which a positive electrode mixture layer was prepared using composite particles in which core particles containing a melamine compound were coated with a polymer having a shell functional group, the resulting positive electrode mixture layer had excellent adhesion, and lithium ion secondary batteries were prepared that were sufficiently safe and had excellent high-temperature storage characteristics. On the other hand, Table 2 shows that the high-temperature storage characteristics of the lithium-ion secondary battery deteriorate in Comparative Examples 1 and 2 in which the positive electrode composite layer was prepared using the melamine compound without forming composite particles. This result supports the idea that even if the melamine compound and the functional layer binder are mixed during the preparation of the conductive material paste or the positive electrode composite layer slurry, composite particles are not formed in the conductive material paste or the positive electrode composite layer slurry. Furthermore, from Table 2, it can be seen that in Comparative Example 3, in which a positive electrode mixture layer was prepared using composite particles in which core particles containing no melamine compound but azobisisobutyronitrile were coated with a polymer having a shell functional group, the safety of the lithium ion secondary battery was reduced. Furthermore, Table 2 shows that in Comparative Example 4, in which a positive electrode mixture layer was prepared using composite particles in which core particles containing no melamine compound but azodicarbonamide were coated with a polymer having a shell functional group, the adhesion of the positive electrode mixture layer was reduced. [Industrial Applicability]

[0136] According to the present invention, it is possible to provide composite particles for electrochemical element functional layers and a binder composition for electrochemical element functional layers that can provide the electrochemical element with excellent high-temperature storage properties while fully ensuring the adhesion of the functional layer and the safety of the electrochemical element. Furthermore, according to the present invention, it is possible to provide a conductive paste for an electrode mixture layer and a slurry for an electrode mixture layer that can sufficiently ensure the adhesion of the electrode mixture layer and the safety of the electrochemical element, while enabling the electrochemical element to exhibit excellent high-temperature storage characteristics. Furthermore, according to the present invention, it is possible to provide an electrode for an electrochemical device that can ensure the safety of the electrochemical device while enabling the electrochemical device to exhibit excellent high-temperature storage characteristics. Furthermore, according to the present invention, it is possible to provide an electrochemical element which is sufficiently safe and has excellent high-temperature storage characteristics. [Explanation of symbols]

[0137] 100 composite particles 110 Core Particle Outer surface of 110S core particle 120 Shell Polymer

Claims

1. A core particle including a melamine compound; a shell polymer covering at least a portion of the outer surface of the core particle and having at least one group selected from the group consisting of a nitrile group, a carboxylic acid group, a hydroxyl group, a sulfonic acid group, an aldehyde group, and an amide group; wherein the core particle has a core-shell structure in which the core particle is covered with the shell polymer.

2. A composite particle for an electrochemical element functional layer as described in claim 1, wherein the proportion of the shell polymer in the total of the core particle and the shell polymer is 0.1 mass% or more and 50.0 mass% or less, with the total of the core particle and the shell polymer being 100 mass%.

3. 3. The composite particle for an electrochemical element functional layer according to claim 1, wherein the shell polymer has a swelling degree in an electrolyte of 100% by mass or more and 600% by mass or less.

4. 4. The composite particle for an electrochemical element functional layer according to claim 1, wherein the thermal decomposition starting temperature is 120° C. or more and 500° C. or less.

5. 5. A binder composition for an electrochemical element functional layer, comprising the composite particles for an electrochemical element functional layer according to claim 1 and a solvent.

6. The binder composition for a functional layer of an electrochemical element according to claim 5 , further comprising a binder for the functional layer.

7. 7. The binder composition for an electrochemical element functional layer according to claim 6, wherein the binder for the functional layer is a polymer having at least one selected from the group consisting of a carboxylic acid group, a hydroxyl group, a nitrile group, an amino group, an epoxy group, an oxazoline group, an isocyanate group, a sulfonic acid group, an ester group, and an amide group.

8. A conductive material paste for an electrode mixture layer, comprising the binder composition for an electrochemical element functional layer according to any one of claims 5 to 7 and a conductive material.

9. A slurry for an electrode mixture layer comprising the conductive material paste for an electrode mixture layer according to claim 8 and electrode active material particles.

10. 10. An electrode for an electrochemical element comprising an electrode mixture layer on a current collector, the electrode mixture layer being a dried product of the electrode mixture layer slurry according to claim 9.

11. An electrochemical device comprising the electrode for electrochemical devices according to claim 10.

Citation Information

Patent Citations

  • High-safety lithium ion battery anode material and preparation method thereof

    CN108134044A

  • Separator for electrochemical device

    JP2016181324A

  • Positive electrode, battery, battery pack, electronic apparatus, electric vehicle, power storage device, and power system

    JP2018129121A

  • Positive electrode for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery

    WO2014119315A1

  • Binder composition for nonaqueous secondary batteries, slurry composition for nonaqueous secondary battery functional layers, functional layer for nonaqueous secondary batteries, and nonaqueous secondary battery

    WO2018155345A1